Plan Evaluation Strategy of the Probolinggo Regency Food Security and Agriculture Service for 2022 (Study of Red Onion Plants in Mranggonlawang Village, Dringu District, Probolinggo Regency) - Marwiyah, Siti; Mubaroq, Husni; Sufri, Sufri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Food and agricultural security is the availability of food and a person's ability to access it. The Probolinggo Regency Food Security and Agriculture Service also supports national food security, by making the agricultural sector one of the regional potentials that continues to be developed. However, there are problems such as the government and community's food reserves not increasing in the Probolinggo Regency area, agricultural human resources (HR) which are still lacking and the agricultural infrastructure program is still not evenly distributed. So it is necessary to focus on increasing the competitiveness of the agricultural sector. How this competitiveness can be achieved is by orienting agricultural activities towards the market (market oriented). It can be seen that the competitiveness of the agricultural sector itself can be realized through increasing productivity and added value. Where this competitiveness can be obtained through 3 components, namely: capital, superior human resources, and superior technology. Even though the majority of farmers in Probolinggo Regency still use traditional technology to medium technology